Empowering Sustainable Household Waste Management through Rubbin: App-Based Transactions using Google Maps API and QR Code Recognition - Rimbawa, H.A. Danang; Arghanie, Muhammad Abditya; Renoult, Muhammad Rey; Ananda, Dea Dwi (Smart City, 2026)
The Digitization of environmentally friendly technology must be applied to advance smart cities. Waste management carried out conventionally often causes irregularities in the classification data collection, difficulties in accessing information related to garbage collection schedules, and a lack of transaction history information, which causes a decrease in the quality of waste collection. The development of functional application features is urgently needed as a container for proper waste management. The Rubbin App has been created, which implements Google Maps API for route optimization and waste mapping, QR code recognition using Enhanced Adaptive Median Filter, and private chat for clients and collectors as additional features. The purpose of designing this research is to overcome the impacts of climate change, significantly reducing gas emissions, by proposing a digital waste management system by providing iOS and Android multiplatform applications with attractive and easy-to-use UI/UX interfaces. The Rubbin application utilizes Google Maps API technology to enable waste tracking and route optimization while employing QR codes to streamline the transaction process between clients and collectors, ensuring efficient waste management operations. The Rubbin application results show a change in the community's waste management habits, forming a culture of caring for the environment.